Efficacy analysis of targeted nanodrug for non-small cell lung cancer therapy - Li, Tongtong; Zhou, Tong; Liu, Ying; Wang, Jingyue; Yu, Zhenxiang (Frontiers in Bioengineering and Biotechnology, 2022)
Biological macromolecules have been widely used as biomedical carriers in treating non-small cell lung cancer (NSCLC) due to their biocompatibility, targeting, biodegradability, and antitumor efficacy. Nanotechnology has been used in clinics to treat many diseases, including cancer. Nanoparticles (NPs) can accumulate drugs into tumors because of their enhanced permeability and retention (EPR) effects. However, the lack of active targeting ligands affects NPs drug delivery. Arginine-glycine-aspartic (RGD), as a targeting ligand, has distinct advantages in targeting and safety. In the present study, an RGD peptide-modified nanogel called RGD−polyethylene glycol−poly (L-phenylalanine-co-L-cystine) (RGD−PEG−P(LP-co-LC−P(LP-co-LC) was investigated to deliver vincristine (VCR) as NSCLC therapy. The VCR-loaded targeted nanoparticle (RGD-NP/VCR) demonstrated excellent antitumor efficacy compared to the free drug (VCR) and untargeted nanoparticle (NP/VCR) without any significant side effects. RGD-NP/VCR has better tumor inhibition and fewer side effects, indicating its potential benefit in NSCLC treatment.